Should Joint Deformity, which is More Common Than Swelling or Tenderness, be Assessed in all Rheumatoid Arthritis Patients and Databases? - Theodore Pincus; Tengfei Li; Kathryn A. Gibson (ACR Open Rheumatology)
Objective We analyzed 28 joint counts in 173 contemporary routine care patients with rheumatoid arthritis (RA), who had disease duration of 10 years and were examined in 2021, for swollen joint count (SJC), tender joint count (TJC)/pain on motion, and deformity joint count (DJC)/limited motion. In addition, we computed DJC according to Disease Activity Score in 28 joints (DA28), Clinical Disease Activity Index (CDAI), and Routine Assessment of Patient Index Data 3 (RAPID3) as remission/low or moderate/high activity or severity. Methods This report presents a retrospective analyses of a cross‐sectional Australian database for medians and prevalences of SJC, TJC, and DJC, including in RA index categories. Results Median values were 0 for SJC, 2.0 for TJC, and 4.0 for DJC, respectively, including SJC of 0,1 in 123 patients (71%), TJC of 0,1 in 82 patients (47%), SJC+TJC of 0,1 in 73 patients (42%), and DJC of 0,1 in 65 patients (38%). Among 4,498 joints, 1,330 with any abnormality included 286 swollen joints (6%), 590 tender joints (13%), 879 deformed joints (20%), 37 only swollen joints (1%), 289 only tender joints (6%), 659 only deformed joints (15%), 458 joints with two abnormalities (10%), and 80 joints with three abnormalities (2%). The 73 of all 173 with patients with SJC and TJC 0,1 (42%), included 56% to 67% who were classified in remission or low DAS28 ESR erythrocyte sedimentation rate, CDAI, or RAPID3 activity or severity, of whom 47% to 58% had DJC ≥2, whereas 11% to 36% were classified as moderate or high RA index activity or severity, of whom 57% to 58% had DJC ≥2. Conclusion SJC+TJC of 0,1 was more common than a DJC of 0,1 in contemporary patients with RA. DJC was ≥2 in the majority of patients who met SJC+TJC remission criteria for RA indices, as in patients who were classified as moderate/high although they met SJC+TJC remission criteria. DJC should be included in long‐term routine care and RA databases.